Impact Assessment for Sustainable Project Management And Pension Funds Projects Performance In Kenya (International Journal of Scientific Research and Management (IJSRM), 2022)
Sustainability is an evolving area of research and is grabbing the attention of corporations, research communities, and regulatory bodies worldwide which had enhanced its implementation. The prevailing trend towards economic growth in developing countries has resulted in a huge demand for delivering construction projects which in turn has overshadowed sustainability concerns. Consequently, project managers in developing countries are lagging in embracing the concept of sustainability in managing projects. Specific focus has been given to construction projects in the pension industry in Kenya. To address this challenge, the paper explored sustainable project management based on a comprehensive literature review through a desk review of numerous academic journal articles to evaluate pension funds projects performance. Three theories were used to provide a foundation for the sustainable project management practices: stakeholder theory, the Triple Bottom Line (3BL) concept which captures the essence of sustainability and theory of risk management. The study established that current project management practices of Kenyan Pension Funds do not always ensure project success that secure desired market returns on these investments. As the pension schemes are also expected to continue to invest in alternative assets given the broadening of the allowable investment categories and to take advantage of the public infrastructural projects under the big four agenda (RBA, 2021), it becomes paramount to identify and implement sustainable project management practices for performance of the pension funds projects. The outcome of this research showed that sustainability goals and environmental and social impact assessment contribute towards pension funds projects performance. The moderating effect of the regulatory framework was determined to be supportive towards sustainable pension funds projects performance.